SISTEM PENDUKUNG KEPUTUSAN PENENTUAN KARYAWAN TERBAIK CARREFOUR MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) - Atin Triwahyuni; M. Reza Septiawan; Rizal - (IIB Darmajaya, 2015)
Carrefour is a company engaged in the field of trade. Carrefour during this procedure uses only the standard recommends employees per Division to include in the determination of the best employees. The assessment is done to determine the best employees of the company must comply with aspects such as mastery of insight into carrefour, mastery of the insight into the activities of the shops, the mastery of an insight into the management of the store, the ability to respond to and answer questions. The company is sometimes difficult in making a decision, especially if some of the existing employees have skills that are not much different the existing problems on the determination of the best employees. Therefore required a decision support system in the determination of the best employees. This research method using Simple Additive Weighting (SAW) are often also known the term weighted summation method. The concept of the method is to find a weighted summation of the SAW of rating performance on any alternative on all attributes. The method of matrix the normalization process requires SAW decision (x) to a scale that can be compared with all the alternative rating. Development of a system that used to use the waterfall. The results of this research in the form of a system that will help employees admin section in performing data processing employees, can automate the penginputan employees and can provide solutions for the employee admin section. Keywords:Simple Additive Weighting (SAW), Assessment, Waterfall